MENGINTEGRASIKAN ASPEK SOSIAL PADA RENCANA PENUTUPAN DAN PASCA TAMBANG - Sutrisno, Agung Dwi; Sumarjono, Erry; Kaifiyah, Anna Sikhatul (KURVATEK, 2022)
Mine closure will have an economic, environmental, and social impact on the surrounding community. Regarding crucial social aspects, this study aims to reveal the perceptions of the community around the mining site, especially in terms of increasing skills for the surrounding community before the mine is closed, socializing mine closure and post-mining plans, encouraging involvement in mine closure and post-mining plans, providing access to business capital, and ex-mining facilities, and creating post-mining job opportunities. The method used is quantitative and analyzed descriptively. The results showed the perceptions of the people around the gold mine of PT. Aneka Tambang (Pongkor) are good, while they are quite the opposite in other aspects. This perception is influenced by the level of education of the respondents. In the future, efforts need to be made to improve the perception of the surrounding community by improving the performance of the other 5 aspects.